2020
DOI: 10.1016/j.artd.2019.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Wearable activity sensors and early pain after total joint arthroplasty

Abstract: A prospective observational cohort of 20 primary total hip arthroplasty (n ¼ 12) and total knee arthroplasty (n ¼ 8) patients (mean age: 63 ± 6 years) was passively monitored with a consumer-level wearable activity sensor before and 6 weeks after surgery. Patients were clustered by minimal change or decreased activity using sensor data. Decreased postoperative activity was associated with greater pain reduction (À5.5 vs À2.0, P ¼ .03). All patients surpassed minimal clinical benefit thresholds of total joint a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 8 publications
0
21
0
Order By: Relevance
“…Increasing use of wearable technology in orthopedic surgery results in a rapid improvement of sensor technology that can be utilized for preoperative evaluation of patients as well as intraoperative guidance and postoperative monitoring and follow-up [ 20 , [23] , [24] , [25] , [26] , [27] , [28] ]. The use of wearable sensors is a safe, rapid, and efficient way to detect pelvic mobility in patients, including those with low back pain or those requiring spinopelvic evaluation [ [36] , [37] , [38] ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Increasing use of wearable technology in orthopedic surgery results in a rapid improvement of sensor technology that can be utilized for preoperative evaluation of patients as well as intraoperative guidance and postoperative monitoring and follow-up [ 20 , [23] , [24] , [25] , [26] , [27] , [28] ]. The use of wearable sensors is a safe, rapid, and efficient way to detect pelvic mobility in patients, including those with low back pain or those requiring spinopelvic evaluation [ [36] , [37] , [38] ].…”
Section: Discussionmentioning
confidence: 99%
“…With an increased interest in noninvasive wearable technology for research and clinical use, there remains a need to validate and determine the most effective, efficient, and accurate devices [ 29 ]. Not only can wearable technology be utilized during the preoperative evaluation process to help guide surgical decision-making, but such devices can be used for direct monitoring of postoperative outcomes and follow-up as well as for evaluation of functional biomechanics [ 20 , [23] , [24] , [25] , [26] , [27] , [28] ]. Studies in the literature evaluating wearable technology for spinopelvic motion analysis report promising results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PGHD has the potential to support personalized health care delivery. For example, using a consumer-level wearable sensor to monitor patients' activity level after total joint arthroplasty, Patterson et al found that patients who were objectively more sedentary early in their recovery experienced less pain without compromising subjective health outcomes measured by PROMs [76] . Actively and passively captured 'digital biomarkers' quantify health status and enable digital phenotyping, defined as the "moment-bymoment quantification of individual human phenotypes in situ using data from personal digital devices, in particular smartphones" [77] .…”
Section: Exploring the Mobile/wearable Technologiesmentioning
confidence: 99%
“…Perraudin et al [70] also studied patients with arthritis but used wearable accelerometers to assess the duration of an unsupervised 5 Times Sit to Stand Test in the morning, and they found that the duration of the test was significantly associated with pain, particularly upon waking and overnight. In relation to postoperative pain, Patterson et al [87] found that decreased postoperative activity was associated with a greater reduction in pain scores among patients who underwent knee and hip replacements.…”
Section: Pain and Wearable Devices: The Promising Road Aheadmentioning
confidence: 99%